45th AIAA Thermophysics Conference 2015
DOI: 10.2514/6.2015-2668
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemistry of CN in the Boundary Layer of Graphite in Nitrogen Plasmas

Abstract: Ablative heat-shield materials are a crucial component of atmospheric entries. Comprehensive experiments in their operative conditions, coupled with numerical work, are fundamental to advance the knowledge of their response for thermal protection system design. Most numerical models describe oxidation and sublimation, but do not treat nitridation of the carbon surface, which may impact surface recession and heat flux. We present experiments of graphite ablation in nitrogen plasmas, produced by the VKI Plasmatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…During air flow ablation tests, it has been already shown that nitridation plays only a minor role in carbon removal [29,30]. We also have checked that sublimation plays a minimal role in the chosen conditions.…”
Section: Diffusion/reaction Competition Analysismentioning
confidence: 96%
“…During air flow ablation tests, it has been already shown that nitridation plays only a minor role in carbon removal [29,30]. We also have checked that sublimation plays a minimal role in the chosen conditions.…”
Section: Diffusion/reaction Competition Analysismentioning
confidence: 96%
“…The reaction probabilities for the two oxidation reactions and the sublimation reaction have been taken from Park, 14 while the nitridation reaction probability is taken from Suzuki 15 based on a recent experimental investigation by Helber et al 16 on the nitridation of Graphite in a pure Nitrogen plasma. Note that the sublimation reaction is considered reversible such that carbon may condense on the surface.…”
Section: Ablation Couplingmentioning
confidence: 99%
“…It predicts a maximum oxidation rate at approximately 2200 K, which corresponds well to the temperatures at which the air results plateaued before then falling. The observation of continually increasing CN emissions for the N 2 condition is significant, as no measurements of the nitridation rate have been made above 2575 K, with the highest temperatures by Helber et al [57]. Despite much variation in the measurements by different authors, it has generally been seen that an Arrhenius formulation is suitable for predicting the nitridation rate.…”
Section: Surface Chemistry Implicationsmentioning
confidence: 92%
“…The measured γ N varied from 3 ×10 −3 at 2140 K to 0.81-1.25 ×10 −3 at 2575 K. To the author's knowledge, this is the highest surface temperature for which nitridation efficiency has been measured. Helber et al [57] created the summary plot shown in Figure 2.6 of all current experimental measurements of γ N , based on a previous plot by Zhang et al [56]. It is clear that there is much discrepancy between the limited number of measurements found in the literature.…”
Section: Nitridationmentioning
confidence: 99%
See 1 more Smart Citation